Identification and Characterization of the Potential Promoter Regions of 1031 Kinds of Human Genes - Suzuki, Yutaka; Tsunoda, Tatsuhiko; Sese, Jun; Taira, Hirotoshi; Mizushima-Sugano, Junko; Hata, Hiroko; Ota, Toshio; Isogai, Takao; Tanaka, Toshihiro; Nakamura, Yusuke; Suyama, Akira; Sakaki, Yoshiyuki; et al. (Genome Research, 2001)
To understand the mechanism of transcriptional regulation, it is essential to identify and characterize the promoter, which is located proximal to the mRNA start site. To identify the promoters from the large volumes of genomic sequences, we used mRNA start sites determined by a large-scale sequencing of the cDNA libraries constructed by the “oligo-capping” method. We aligned the mRNA start sites with the genomic sequences and retrieved adjacent sequences as potential promoter regions (PPRs) for 1031 genes. The PPR sequences were searched to determine the frequencies of major promoter elements. Among 1031 PPRs, 329 (32%) contained TATA boxes, 872 (85%) contained initiators, 999 (97%) contained GC box, and 663 (64%) contained CAAT box. Furthermore, 493 (48%) PPRs were located in CpG islands. This frequency of CpG islands was reduced in TATA+/Inr+PPRs and in the PPRs of ubiquitously expressed genes. In the PPRs of the CGM2 gene, the DRA gene, and theTM30pl genes, which showed highly colon specific expression patterns, the consensus sequences of E boxes were commonly observed. The PPRs were also useful for exploring promoter SNPs.[The nucleotide sequences described in this paper have been deposited in the DDBJ, EMBL, and GenBank data libraries under accession nos.AU098358–AU100608.]